Anatomy and Physiology 2 Lab Manual - Shook, Sheryl (Open textbook library., 2022)
This manual is a guide for anatomy and physiology laboratory exercises. It includes dissection guidance with detailed images; instructions for physiology experiments including foundational content; and gross anatomy study guides for six body systems. Videos and tutorial links provide additional support.